Video Game Preferences and Their Impact: Aggression and Sexualization Exposures among Indonesian Millennials - Yolanda Ghea; Andika Putra Pratama (Fakultas Seni Rupa dan Desain ITB, 2023)
For years, the world of games has impacted people’s lives and become one of the largest industries in the world. In 2022, most gamers will be Millenials who know what kind of game they prefer and its effects on their lives, which might help them understand how the world of games evolved. For this reason, the conjoint survey is being conducted to understand the Millenials’ game preferences. The quantitative data was gained from 111 respondents from Indonesia using the conjoint method, where the country holds the record of being the third-biggest country in the world in which gamers reside. The attributes of importance and the preference of levels analyzed by conjoint analysis showed that the most likable game preferences for Indonesian Millennials are single- player, free, online, computer, or mobile format games. The result of this research also recommends that the game industry reconsider its exposure to violence and sexualization toward gamers since a quarter of their consumers experienced disturbing effects on their mental health as a result of the game they played.